Cooperative intelligent transport systems : towards high-level automated driving. (Transportation, 2019)
The book provides a comprehensive insight in the state of the art of C-ITS and automated driving, especially addresses the role of ICT (Information and Communication Technologies) infrastructure, and presents the main achievements (both theory and practice), as well as the challenges in the domain in Europe, the US and Asia/Pacific.